Meg and A Man for All Seasons: A Study of History - Rasha Abdulmunem Azeez (مجلة الباحث, 2025)
This research paper shows how history is sometimes distorted to convey a different story, not a real one. This distortion is tackled to highlight the character of Meg from a feminist point of view. The argument is based on the theory of adaptation; Paula Vogel adapts Robert Bolt's A Man for All Seasons to write her play Meg. The aim of this paper is to disuss how Vogel shows in her play that rewriting history might disclose important facts through the theory of adaptation; in the case of Meg, it presents a powerful, smart woman who can take decisions and be completely independent. While readers do not meet Meg or Margaret only for few times in A Man for All Seasons because she is meant to be marginalized as a secondary character, Meg in Vogel's Meg is the central character who controls the whole action of the play, reporting a different historical fact concerning a female figure.